The Influence of Cube Puzzle Media on Cultural Diversity of Social Studies Learning Content on Learning Creativity and Learning Outcomes of Class V Students at Pampang Elementary School - Fadliani, Fadliani; Yunus, Muh; Yahya, Muh (CV. Rayyan Dwi Bharata, 2025)
This research aims to analyze and examine 1) the influence of the Cultural Diversity Cube Puzzle Media in Social Sciences Learning Content on Learning Creativity and Learning Outcomes of Class V Students at Pampang Elementary School. This type of research is quasi experimental research. The population of this study were all class V students at SDN Pampang with a total of 63 students. The sample was taken from 1 class as a control class, namely class VA with 24 students and 1 class as an experimental class, namely class VB with 24 students. Data collection techniques use research questionnaires, tests and documentation, while data analysis techniques use descriptive analysis and t tests. The results of the research show that 1) the Cube Puzzle Media model Cultural Diversity of Social Studies Learning Content has an influence on the Learning Creativity of Class V Students at SD Pampang. This research uses descriptive statistical analysis where the control class has an average of 50.12 and the experimental class has an average value 56, where the average has increased. To test the hypothesis in the control class and experimental class both increase Learning Creativity or there is no difference in the average before and after treatment in either the control class or the experimental class because they have a p-value 0.05. 2) there is an influence of the Cube Puzzle Media model on Cultural Diversity of Social Sciences Learning Content on Improving Learning Outcomes for Class V Students at Pampang Elementary School. This research uses descriptive analysis where the control class has an average on the Pre Test, namely 51.70 and Post Test, namely 55.45, while the experimental class has an average on the Pre Test, namely 45.66 and Post Test, namely 74.33. where in the experimental class there was a very high increase in learning average. To test the hypothesis, there is a difference in the average learning outcomes of social studies learning before and after learning Cube Puzzle Media with a p-value 0.05.